A new species of Acaudinum Börner (Hemiptera; Aphididae; Aphidinae) from Kazakhstan - Kadyrbekov, Rustem Kh. (Zootaxa, 2022)
The new species Acaudinum (Acaudinum) rogeri sp.n. is described from Kazakhstan from Serratula coronata L. The new species is close to A. (Acaudinum) longisetosum Holman, 1970 and A. (Acaudinum) roumanicum Holman, 1991. It differs from both species in the proportion of the length of the last rostral segment to the length of the second segment of the hind tarsus (1.47–1.71 versus 1.22–1.55), the number of accessory setae on the last segment of the rostrum (4–6 versus 2–5). Fewer setae on the anterior margin of the genital plate (8–10 and 10–24). It also differs from A. longisetosum in the ratio of siphunculi length to body length (0.13–0.20 versus 0.20–0.30), in having fewer setae on the cauda (10–12 and 13–17), and 8th abdominal tergite (4–6 in comparison with 5–9). From A. roumanicum with a longer second segment of the hind tarsus (0.14–0.19 mm and 0.12–0.15 mm). From A. centaureae (Koch, 1854) it is distinguished by setae on trochanters, femora, and ventral side of the body which is long and thin, and a fodder plant belonging to another genus of Asteraceae family. A comprehensive key to distinguish apterous viviparous females based on existing keys is provided.